GAMBARAN ASUPAN ZAT BESI DAN STATUS GIZI PADA REMAJA PUTRI - Siti Nur Fatinah; Anna Yuliastani Pomalingo (JOURNAL HEALTH AND NUTRITIONS, 2021)
Iron is an essential microelement for the body. This substance is especially needed in hemopoboesis (blood formation), namely the synthesis of hemoglobin (Hb) an oxygen that delivers erythrocytes to function important for the body. Hemoglobin consists of Fe (iron), protoporphyrin, and globin (1/3 weight of Hb consists of Fe). Objective of the study was describe the iron intake and nutritional status of adolescent girls in Dutohe Barat Village, Bone Bolango Regency. Research methods was used a descriptive survey, which is a survey conducted to describe the variables studied. The population was 83 people, with a sample that meets the inclusion criteria of 40 people. The results was showed that all young women (100%) in Dutohe Barat Village had less iron intake. Adolescent girls with good nutritional status are 37 people (92.5%), overweight are 2 people (5%), and obese are 1 person (2.5%). Conclusion was all young women as a subject in the study have low iron intake, while the majority of their nutritional status (BMI/U) was in good category. ABSTRAK  Zat besi merupakan mikroelemen yang esensial bagi tubuh. Zat ini terutama diperlukan dalam hemopoboesis (pembentukan darah) yaitu sintesis hemoglobin (Hb) suatu oksigen yang mengantarkan eritrosit berfungsi penting bagi tubuh. Hemoglobin terdiri dari Fe (zat besi), protoporfirin, dan globin (1/3 berat Hb terdiri dari Fe). Tujuan Penelitian : untuk mengetahui gambaran asupan zat besi dan status gizi pada remaja putri di Desa Dutohe Barat Kabupaten Bone Bolango. Metode penelitian ini menggunakan survey deskriptif, yaitu survey yang dilakukan untuk menggambarkan variabel yang diteliti. Populasi berjumlah 83 orang, dengan sampel yang memenuhi kriteria inklusi sejumlah 40 orang. Hasil penelitian menunjukkan bahwa semua remaja putri (100%) memiliki asupan zat besi kurang. Remaja putri berstatus gizi baik berjumlah 37 orang (92,5%), gizi lebih berjumlah 2 orang (5%), dan obesitas berjumlah 1 orang (2,5%). Kesimpulan seluruh remaja putri memiliki asupan zat besi dengan kategori kurang, sedangkan mayoritas status gizinya (IMT/U) berkategori baik.